Survival outcomes of autologous breast reconstruction after mastectomy: A matched case-control study - Wu, Shang; Ma, Xindi; Zhang, Xiangmei; Yang, Chao; Wang, Yubin; Liu, Yunjiang (Frontiers in Oncology, 2023)
Background Due to the lack of strong evidence-based medical evidence, the relationship between autologous breast reconstruction (ABR) after mastectomy and long-term prognosis is unclear. This study aims to explore if ABR after mastectomy is associated with the prognosis of breast cancer (BC) patients based on the data from the Surveillance, Epidemiology, and End Results (SEER) database. Methods We collected data for all cases diagnosed with BC who underwent or did not undergo ABR after mastectomy from 2010-2015 in the SEER database. The primary outcome of our study was overall survival (OS) and cancer specific survival (CSS). The Propensity Score-Matched (PSM) analysis was used to eliminate the effects of non-random statistics, setting the caliper as 0.0001 to balance the baseline variables within the groups. Chi-square test, Kaplan-Meier method, univariate and multivariate cox regression analysis were used to analyze the data and subgroup analysis was performed to find the subgroups of people who might benefit from ABR. Result Of 27893 eligible patients, 11038 patients were matched. The cohort consisted of 5519 (50%) ABR patients and 5519 (50%) non-ABR patients after PSM. After PSM, on multivariate cox regression analysis, ABR still exerted a significant influence on the OS (hazard ratio (HR), 0.83, P< 0.05). However, no statistical difference was shown on CSS (HR, 0.93, P = 0.31). Kaplan-Meier survival analysis showed ABR group had better OS (P = 0.001), but similar CSS (P = 0.174) between ARB and mastectomy groups. Subgroup analysis showed that after matching, those with 50-59 years old, earlier stages of disease, without a marital partner and living in urban areas had better OS after ABR. Conclusions ABR after mastectomy was associated with better OS, but not affect CSS.